Pengaruh Penggunaan Paylater terhadap Sikap Konsumtif Mahasiswa Universitas Jambi dalam Perspektif Ekonomi Islam - Ary Dean Amri; Allif Al Fattahillah; Chealsy Amanda; Hadiah Tri Marlia Putri; Nurul Adila; Pandu Syahrez Alkautsar (Universitas Batanghari Jambi, 2023)
Based on a preliminary survey conducted by researchers of 100 students of the Faculty of Economics and Business, University of Jambi using a questionnaire distributed online via Google Form, it was found that 78 students agreed that paylater affects consumptive behavior. And the results of a research study conducted by researchers also show that 97 students use Shopee PayLater with the slogan